(untitled) (In situ, 2024)
In 2023, systematic research of the ship Trstenik 3 began. Sampling of the wood used for the ship structure was carried out on the ship Trstenik 2. The ship Trstenik 3 has been completely cleaned of stones and sediment, but fine cleaning needs to be carried out during the next research campaign. The overall length of the ship is about 11 m, and the greatest width is about 3.5 m. Thirty-four frames have been preserved, consisting of floor timbers or half frames and futtocks. Simultaneously with the research of the ship Trstenik 3, the remains of the ship Trstenik 2 were uncovered, with the aim of systematic sampling of the wood of which the ship was built. Upon completion of the work, long-term in situ protection of the ship was carried out.